Pengembangan Materi pembelajaran Keberagaman Budaya Menumbuhkan Kesetiaan Terhadap Tanah Air pada Siswa Kelas IV SD - Nurlaila Ramadhani; Ramanda Putri Mardiyyana; Tin Rustini (Pusat Riset dan Inovasi Nasional, 2024)
This article is constructed around the discoveries made during the research, where it was found that the character of love for one's country is not yet fully implied in the souls of students. There are still many students who lack discipline in doing and submitting assignments, not only that, there are also many students who speak inappropriately and are impolite to their classmates and those above them, and never care about friends who are experiencing difficulties. The role of learning media is very crucial in helping students understand learning material. To develop learning materials, of course learning media is needed as a supporting tool when learning takes place, with learning media being able to develop material on cultural diversity to increase love for the country, especially focused on class students.